Growth and initial development of Musa textilis Née and its interaction with the timber species Cordia alliodora, Hieronyma alchorneoides and Dipterix panamensis in Costa Rica - Araya-Salas, Mónica (2022)
Musa textilis known in Costa Rica and another countries as abaca, is a species of the Musaceae family which has been commercially cultivated for its ability to produce industrial quality fiber. A key factor for the rural economy of Costa Rica is to increase the productivity and quality of the fiber and to optimize management and harvesting costs. The present work seeks to generate valid results on the positive effect of the interaction of timber trees in an agroforestry arrangement with abaca, with special interest in the future effect of shade on the growth of all species and on fiber quality. In the literature there are few studies that analyze the value of the interaction of the abaca crop with trees in terms of their growth and physiological development. Therefore, this study presents preliminary results of the effect of shading by three native timber tree species on the growth of abaca. For this purpose, monthly measurements of growth (diameter and total height) and physiological development were made SPAD measurements. The hypothesis is that there is a significant positive effect (increase) in the growth and development of all species established with shade, showing significant differences in the long term in each of the shading treatments. In general, it was found that there are significant differences between the growth in height for the plants established in association with timber species and the control plants.